Challenges of human and space mobility in the municipality of Serra/ES in contemporaneity - PEREIRA AROEIRA SUCE, DOURINE; DADALTO, MARIA CRISTINA (Geografares, 2017)
This article aims to discuss the phenomenon of human mobility in the recent history of the municipality of Serra, Espírito Santo. The reflection is developed by analyzing the interface between the processes of industrialization, migration and the pattern of spatial inequality in the place between the years 1960 and 2010. It has as source bibliographical and documentary research with adoption of primary and secondary sources. Is parts of the assumption that the migratory phenomenon established there has a labor perspective and is fed by the network of exchanges and circularity of ideas among migrants. It evaluates that the city, dominated by the logic of capital, manifests the population increase, the discard of the labor force, and produces a social debt that reverberates in the present time.Keywords: Serra; Migration; Inequalities.